2020
DOI: 10.3846/jbem.2020.13978
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Personal Financial Planning Towards Retirement

Abstract: One problem for sustainability of systems pensions is how people without specialized financial training could manage their resources and their actual personal intentions towards retirement. Research objective is to analyse the relationship among several factors that affect the behaviour towards retirement, the financial management practices and the financial resources, by carrying out a structural equation model (SEM) that was tested in Spanish workers sample in three phases. The influence of financial litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 79 publications
(96 reference statements)
0
9
0
3
Order By: Relevance
“…Such practices help them to be more prepared for retirement, consequently leading to higher retirement confidence. Further, studies have found financial management practices to be the major factor to influence retirement confidence [6] and financial resources for retirement [34].…”
Section: Financial Management Practicesmentioning
confidence: 99%
“…Such practices help them to be more prepared for retirement, consequently leading to higher retirement confidence. Further, studies have found financial management practices to be the major factor to influence retirement confidence [6] and financial resources for retirement [34].…”
Section: Financial Management Practicesmentioning
confidence: 99%
“…It is also worth highlighting that each person has behavioral and socioeconomic characteristics that may influence financial preparation for retirement. Social, financial, and psychological factors influence the perception of adequate income for retirement (Herrador-Alcaide et al, 2021;Hershey et al, 2012) and there are significant differences in financial preparation for retirement between various socioeconomic and demographic profiles. There is no consensus on differences in financial preparation for retirement according to sex (Kumar et al, 2019;Noone et al, 2010) and age (Agabalinda & Isoh, 2020;Witvorapong et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…É importante destacar, ainda, que cada indivíduo apresenta características comportamentais e socioeconômicas que poderão influenciar na preparação financeira para aposentadoria. Fatores sociais, financeiros e psicológicos influenciam a percepção da renda adequada à aposentadoria (Herrador-Alcaide et al, 2021;Hershey et al, 2012) e existem diferenças significativas de preparação financeira para aposentadoria entre diferentes perfis socioeconômicos e demográficos. Não existe um consenso sobre as diferenças de preparação financeira para aposentadoria segundo o sexo (Kumar et al, 2019;Noone et al, 2010) e a idade (Agabalinda & Isoh, 2020;Witvorapong et al, 2022).…”
Section: Introductionunclassified